A arte de contar histórias como propositora de teatralidade e afeto - Batista, Jacqueline Patricia Alves (2020)
This dissertation presents my research trajectory’s reflection about the art of telling stories as a theatricality and affection proposer between teacher and elementary school children. What inspired me to follow this path was get to undertand, recognize and base my practice in classroom, inserting it in the theoretical-methodological’s field of Theater’s Pedagogy. Reflections about relations that emerge among the involved bodies in the artistic process, whose are mediated for the orality, narrative and theatricality, made possible to undertand some of the connections between artistic experience and affection in the school context. In order to carry out such reflections, some questions went through me: What am I doing in classroom is really relevant and based in the Theater’s Pedagogy? Does the storytelling enables the affection construction? Does my practice considers affect, memory and history as a constituent of the bodies that I interact? Can the theatricality we share in classroom gives voice and body to the student’s affective and emotional dimensions? Those questions were constantly presents in my theorical studies and allowed me to understand that the experiences of telling, listening and participating of the story’s criation experiences can be the time and space whose children have the opportunity to place themselves physically and emotionally, in the many formation contexts in which they go through. In this way, narrative situations become time and space for experience and freedom for the children and the teacher, setting up as action’s spaces and brigdges to access cognitive and affective knowledge’s fields among those who share this artistic activity.